Benzodiazepine-conjugated pectin hydrogel beads: A controlled and targeted anticancer oral delivery system - Narges Zokaei Golestan; Siamak Javanbakht; Ahmad Shaabani; Mohammad Taghi Nazeri; Fahimeh Kazeminava (Results in Chemistry, 2025)
This study was designed to improve the bioactivity of pectin (Pec) by covalently functionalizing it with benzodiazepine (Benz) via a green and efficient Mannich multicomponent reaction. The resulting Benz-functionalized pectin (Benz-Pec) was subsequently incorporated into a calcium-crosslinked hydrogel bead formulation to serve as an oral delivery system (ODS) for the anticancer drug 5-fluorouracil (5-Fu). The Benz-Pec conjugate exhibited favorable characteristics, including enhanced structural stability, bioactivity, and responsiveness to pH changes. Comprehensive characterization confirmed the successful functionalization of Pec and the formation of uniform hydrogel beads. The formulated Benz-Pec/Pec beads demonstrated pH-sensitive swelling behavior (5.8 at pH 1.2, 8.0 at pH 6.8, and 6.0 at pH 7.4), controlled drug release profiles (30 %, 50 %, and 98 % release at pH 1.2, 6.8, and 7.4, respectively), and superior cytotoxicity against colon cancer HT29 cells, with cell viability reduced to below 42 %. These results indicate that the developed Benz-Pec/Pec hydrogel beads possess strong potential as dual-functional oral carriers for targeted colon cancer therapy.